Studies on Schismatoglottideae of Borneo LXVIII: two new species of Schismatoglottis endemic to the Danum Valley Conservation Area, Sabah, Malaysian Borneo - Peter C. Boyce; Sin, Yeng Wong; Kartini Saibeh (Firenze University Press, 2019)
Schismatoglottis clivemarshii and Schismatoglottis priapica are described and illustrated as new species from the Danum Valley Conservation Area, Tawau, Lahad Datu, Sabah, to where both are endemic.